Os pés da memória: uma etnografia sobre as plantas, o gado e o tempo na beira do rio São Francisco - Acypreste, Izadora Pereira (2021)
This dissertation seeks to discuss, through an approach about plants, cattle and time [tempo], how the life of riverine quilombolas is produced through continuous multispecific engagements. Residents of areas [áreas] along the São Francisco river [beira do rio], the quilombolas of Sangradouro Grande, Croatá, Gameleira and Várzea da Cruz, communities located in the municipality of Januária, North of Minas Gerais, highlight the very importance of the river in the constitution of the landscape, which is also produced by the daily conviviality [convivência] between people, plants and other living beings [viventes]. Therefore, it is through the engagements between people and these other living beings that we can understand the story [estórica] of the constitution of the landscape, which involved, and still involves, several movements, receptions [acolhidas], help [ajudas], among other reciprocal exchanges between humans and non-humans. But this landscape has been changing over time, changes that can be observed from the conviviality with the living beings of the place and against which one can also resist through alliances with each other. Since the plants are deeply intertwined with the way that riverine quilombolas understand their territories, the proposal is to describe these different connections it establishes with the lives of those who, along with them, cohabit along the riverbank. Thus, these “wonderful things” or “lovely things”, as the people on the riverbank say, serve us here not only as a starting point, but also as a common thread that connects the different discussions that make up the thesis. Through this approach, I hope to capture the most sensitive aspects of the way local residents think and relate to their plants [pés], and how, based on this relationship, they conceive and produce other aspects of their lives. In short, I aim to understand what multispecies relationships say about the way of life, the story, the territorialities, and the conviviality that generates bonds of belonging among the inhabitants of these riverine quilombola communities.